2018
DOI: 10.1176/appi.neuropsych.16120328
|View full text |Cite
|
Sign up to set email alerts
|

Guanfacine Attenuates Adverse Effects of Dronabinol (THC) on Working Memory in Adolescent-Onset Heavy Cannabis Users: A Pilot Study

Abstract: The cannabinoid-1 receptor (CB1R) agonist Δ9-tetrahydrocannabinol (THC), the main psychoactive constituent of cannabis, adversely effects working memory performance in humans. The α2A-adrenoceptor (AR) agonist guanfacine improves working memory performance in humans. The authors aimed to determine the effects of short-term (6 days) treatment with guanfacine on adverse cognitive effects produced by THC. Employing a double-blind, placebo-controlled crossover design, the cognitive, subjective, and cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…Future studies are needed to identify if the endocannabinoid system may modulate other aspects of memory such as episodic, semantic, and procedural memory. Our finding that chronic THC had no effect on spatial or non-spatial memory performance is consistent with findings from human literature showing that THC has no effect on memory performance when administered chronically (Mathai et al 2018). However, future studies are needed to investigate the chronic effects of THC in placebo-controlled trials in order for this to be quantitatively investigated.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Future studies are needed to identify if the endocannabinoid system may modulate other aspects of memory such as episodic, semantic, and procedural memory. Our finding that chronic THC had no effect on spatial or non-spatial memory performance is consistent with findings from human literature showing that THC has no effect on memory performance when administered chronically (Mathai et al 2018). However, future studies are needed to investigate the chronic effects of THC in placebo-controlled trials in order for this to be quantitatively investigated.…”
Section: Discussionsupporting
confidence: 93%
“…This finding was not influenced by rodent species, sex, paradigm, drug administration timing, dose, age or the compound used. While further studies are needed to investigate the chronic effects of THC in humans, a single study found that THC (10–20 mg) had no effect on verbal memory performance in humans when administered chronically for 7 days (Mathai et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that guanfacine may also be useful in addressing addiction to cannabis. Guanfacine treatment was shown to reduce the cognitive impairment induced by THC ( Mathai et al, 2018 ), and new data suggest that it may be helpful in treating cannabis addiction ( Dakwar et al, 2020 ), although there are mixed results regarding its effects on withdrawal symptoms ( Haney et al, 2019 , Holst et al, 2019 ). As cannabis use in adolescents is a risk factor for subsequent schizophrenia ( Hasan et al, 2020 ), guanfacine treatment may also be protective in the prodrome to mental illness in high risk adolescents who are cannabis users.…”
Section: Guanfacine Treats Pfc Cognitive Disorders In Humansmentioning
confidence: 99%
“…Daily administration of the compound significantly reduced irritability, produced small but significant decreases in blood pressure and heart rate, however was well tolerated, producing no sedation, dizziness, or altered food intake observed with lofexidine. Due to these results, guanfacine hydrochloride stands out as one of the first non-cannabinoid agonists to reduce cannabis abstinence-related irritability [64,70].…”
Section: α2a Adrenergic Receptor Agonistmentioning
confidence: 99%